Acute Liver Failure following a Single Dose of Atezolizumab, as Assessed for Causality Using the Updated RUCAM. (23rd March 2022) - Tzadok, Roie; Levy, Sharon; Aouizerate, Jessie; Shibolet, Oren
Abstract : Immune checkpoint inhibitors have become major therapeutic agents in oncology over the last few years. However, they are associated with a variety of potentially severe autoimmune phenomena. We present a patient with advanced adenocarcinoma of the lung, who presented with acute liver injury two weeks following his first treatment with atezolizumab, rapidly deteriorating to fulminant liver failure. A thorough evaluation of infectious, vascular, metabolic, and autoimmune etiologies did not yield any results. Liver pathology was nonspecific. Using RUCAM as a causality assessment method indicated probable connection between atezolizumab and liver damage. To our knowledge, this is the first documented report of a patient developing acute liver failure shortly after immune checkpoint inhibitor initiation.